Determining Critical Contributory Factors of Payment Default in Residential Construction Projects - Masrom, Md. Asrul Nasid; Bak Ying, Chong; Mohamed, Sulzakimin; Md Yassin, Azlina; Ta Wee, Seow; Che Haron, Roziha; Chan, Melissa (International Journal of Integrated Engineering, 2021)
Issues in relation to payment is not new and it has always been debated widely in construction contracts research discipline. Payment default is one of a crucial issue that refers to the situation whereby the claimant claims the amount of payment, but they are not being paid in a whole or in part within a specific time (including under payment, delayed payment, and non-payment). In this case, majority of the contractor would be the direct and enormously affected party, however, this area is still under discovered empirically. This research aims to identify factors significantly contributing to the payment default, specifically in private construction projects. Survey was used in this research through questionnaire surveys. The targeted respondents were G7 contractors who have been involved in private projects, mainly in residential projects. The findings address that factor of delay in certification or poor documentation rated the highest average mean value. Meanwhile, the CIDB Standard Form of Contract for Building Works 2000 Edition was determined as the highest average mean value out of five remedies. The outcomes of the study could be useful for the key parties in project to enhancing their understanding and commitment in mitigating payment default issues in private construction projects.